ANALISA YURIDIS PENERBITAN SERTIPIKAT HAK MILIK ATAS TANAH YANG SALING TUMPANG TINDIH - Mussen Aldrin Hasugian; Yetti Yetti; Yeni Triana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Certificate of Ownership Rights (SHM) is proof of land ownership. The method used in this research is Normative Legal Research. The overlap in the issuance of Land Ownership Certificates is contrary to the provisions of Government Regulation Number 24 of 1997 concerning Land Registration and General Principles of Good Governance as stated in the decision of the Pekanbaru State Administrative Court Number 12/G/2023/PTUN.Pbr , the decision of the Medan State Administrative Court Number 107/G/2022/PTUN.Mdn, and the Decision of the Jambi State Administrative Court Number 13/G/2024/PTUN.Jbi. The overlapping legal consequences of the issuance of Certificates of Ownership Rights for land are based on the decision of the Pekanbaru State Administrative Court Number 12/G/2023/PTUN.Pbr, the decision of the Medan State Administrative Court Number 107/G/2022/PTUN.Mdn, and the Court Decision Jambi State Administration Number 13/G/2024/PTUN.Jbi The Panel of Judges granted the Plaintiff's lawsuit and canceled the Certificate of Ownership of the Intervening Defendant which was the object of the dispute and ordered the Head of the Land Office (National Land Agency) to revoke the Certificate of Ownership.Keywords: Land, Certificate, Overlap.